Pengaruh Strategi Belajar MURDER Terhadap Hasil Belajar Siswa Kelas III Matapelajaran Matematika di MI As-Shaffah Kota Bengkulu - Adelia Putri Lestari; Mutiara Tanjung; Meldiana (JPT : Jurnal Pendidikan Tematik, 2025)
This study aims to determine the effect of the MURDER learning strategy on the mathematics learning outcomes of grade III students at MI As-Shaffah, Bengkulu City. The MURDER strategy is an acronym for Mood, Understanding, Recall, Digest, Expand, and Review, which is designed to increase active involvement and understanding of students through systematic and enjoyable learning stages. The research method used is a quantitative approach with a quasi-experimental design in the form of a pretest-posttest control group design. The research sample consisted of two groups: the experimental class treated with the MURDER strategy and the control class with conventional learning. Data collection was carried out through learning outcome tests and observation instruments for student activities, learning implementation, and student response questionnaires. The results showed a significant increase in the experimental group, with an average score of 24.3 points, higher than the control group which only reached 11.2 points. The t-test showed a statistically significant difference (p <0.05), indicating that the MURDER strategy has a positive impact on students' mathematics learning improve student learning outcomes at the elementary school level